Analysis of Internal Audit Practices and Organizational Commitment Towards the Effectiveness of Internal Control and Its Impact on Fraud Prevention In BUMN - Surya Winata, Dedy; Hidayah, Nurul (Lafadz Jaya Publisher, 2024)
BUMN, as a state-owned company, aims to gain profit and provide services and benefits to the community. However, BUMN governance has been in the spotlight due to the rampant corruption cases, such as those that occurred in Jiwasraya and Asabri. Data from the KPK shows that between 2017 and 2023, there were 143 corruption cases in BUMN/BUMD. This study aims to examine and analyze the influence of internal audit practices and organizational commitment on the effectiveness of internal control and fraud prevention in BUMN. The research method uses associative causal with a quantitative approach. Data analysis was carried out using Partial Least Square Structural Equation Modeling (PLS-SEM) with the Smart PLS application. The research instrument used a questionnaire with respondents of the Audit Board of Indonesia (BPK) who conducted audits of BUMN, so that it is expected to provide more independent answers for measuring each variable. The results of the study indicate that internal audit practices have a significant positive effect on the effectiveness of internal control and fraud prevention. Organizational commitment also has a significant positive effect on the effectiveness of internal control, but does not have a significant effect on fraud prevention. Internal control effectiveness does not mediate the effect of internal audit practices or organizational commitment on fraud prevention. The implications of the research results are the importance of improving internal audit practices and organizational commitment as an effort to improve the effectiveness of internal control, although the implementation of fraud prevention requires an additional integrated approach.